Fetometry in Arabian horses - Ali, Ahmed; Derar, Derar R.; Alaeyeari, Ahmad A.; Alharbi, Yousef M. (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to monitor intrauterine fetal growth, establish predictive equations for gestational age estimation, and determine the optimal period for fetal sexing in Arabian horses using ultrasonography.Materials and methodsSeven Arabian mares were monitored from insemination to parturition using transrectal ultrasonography. The following fetal and embryonic parameters were measured: embryonic vesicle (EV), crown–rump length (CRL), biparietal diameter (BIP), stomach diameter (STD), chest depth (CHD), abdominal diameter (ABD), kidney length (KDL), eyeball diameter (EBD), and eye lens length (ELL). Key developmental milestones were recorded, including detection of the EV, embryo proper, organization, and ossification.ResultsThe EV, embryo proper, organization, and ossification were visualized at days 10.3 ± 0.5, 21.3 ± 1.3, 33.6 ± 2.0, and 57.7 ± 3.5, respectively. All biometric parameters, except CRL, ELL, and KDL, exhibited strong linear correlations with gestational age (P < 0.0001). Fetal sexing was feasible between days 56 and 161, with maximum accuracy (98%) and applicability (64.9%) between days 105 and 133.Discussion and conclusionUltrasonographic monitoring provides reliable parameters for assessing fetal growth and estimating gestational age in Arabian horses. The period between days 105 and 133 of gestation represents the optimal window for accurate fetal sex determination. These findings enhance reproductive monitoring and breeding management practices in Arabian horse herds.